Alloy powder, compound, alloy steel preparation method, rotating shaft and electronic equipment

By improving the composition ratio of alloy powder and optimizing the MIM process, the problem of low density of low-carbon alloy steel is solved, and high-strength and high-toughness alloy steel is achieved to meet the needs of high-performance parts.

CN119501048APending Publication Date: 2025-02-25BEIJING XIAOMI MOBILE SOFTWARE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311068388.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Low-carbon alloy steels prepared by existing MIM technology are difficult to meet the requirements of high strength and high toughness at the same time, mainly due to the low grain density.

Method used

By improving the composition ratio of alloy powder, especially controlling the proportion of carbon elements within a reasonable range, the density of low-carbon high-alloy steel formed by alloy powder is increased, thereby improving its strength and elongation. The specific steps include mixing the alloy powder with the binder, performing kneading, injection molding, catalytic degreasing, partial pressure sintering and heat treatment.

Benefits of technology

The strength of alloy steel exceeds 1800MPa and elongation exceeds 6%, meeting the needs of high-performance parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides alloy powder, a compound, a preparation method of alloy steel, a rotating shaft and electronic equipment, the alloy powder comprises, by mass, 0.03 wt%-0.25 wt% of C, 5.00 wt%-6.00 wt% of Ni, 4.00 wt%-6.00 wt% of Mo, 9.00 wt%-11.00 wt% of Cr, 8.00 wt%-10.00 wt% of Co and the balance Fe, and the mass percentage ratio X1 = (Cr + Mo) / C is 12-566. According to the low-carbon high-alloy steel and the preparation method thereof disclosed by the invention, the density of the low-carbon high-alloy steel formed by the alloy powder is improved by improving the proportion of powder components for forming the alloy steel, so that the strength and the elongation of the low-carbon high-alloy steel are improved, the strength of the low-carbon high-alloy steel can exceed 1800MPa, the elongation of the low-carbon high-alloy steel exceeds 6%, and the requirements of high-performance parts are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technical field involved in the present disclosure particularly relates to a method for preparing alloy powder, composite material, alloy steel, a rotating shaft and electronic equipment. Background Art

[0002] Metal Injection Molding (MIM) technology is a new powder metallurgy molding technology that introduces modern plastic injection technology into the field of powder metallurgy. MIM technology uses mold injection molding blanks and quickly manufactures high-precision, three-dimensional complex parts through sintering to meet the needs of communication equipment shafts, military equipment parts, high-voltage sensors, etc.

[0003] With the in-depth application of MIM products in various fields, the demand for the strength and toughness of MIM materials is constantly increasing. At present, the yield strength of low-carbon alloy steels produced by MIM technology is mostly around 1500MPa, and the elongation is mostly around 6%, which makes it difficult to meet the requirements of high strength and high toughness at the same time. Summary of the invention

[0004] In order to overcome the problems existing in the related art, the present disclosure provides an alloy powder, a composite, a method for preparing alloy steel, a rotating shaft and an electronic device.

[0005] According to a first aspect of the present disclosure, an alloy powder is provided, wherein the alloy powder comprises, in terms of mass percentage:

[0006] C: 0.03wt%-0.25wt%;

[0007] Ni: 5.00wt%-6.00wt%;

[0008] Mo: 4.00wt%-6.00wt%;

[0009] Cr: 9.00wt%-11.00wt%;

[0010] Co: 8.00wt%-10.00wt%;

[0011] Fe: remainder;

[0012] Among them, the mass percentage ratio X1=(Cr+Mo) / C is 12-566.

[0013] In some embodiments of the present disclosure, the alloy powder comprises, by mass percentage:

[0014] C: 0.05wt%-0.25wt%;

[0015] Ni: 5.20wt%-5.80wt%;

[0016] Mo: 4.50wt%-5.50wt%;

[0017] Cr: 9.50wt%-10.50wt%;

[0018] Co: 8.50wt%-9.50wt%;

[0019] Fe: remainder;

[0020] Among them, the mass percentage ratio X1=(Cr+Mo) / C is 56-320.

[0021] In some embodiments of the present disclosure, the particle size of the alloy powder is 4-20 μm.

[0022] According to a second aspect of the present disclosure, a composite is provided, the composite comprising alloy powder and a binder, the alloy powder comprising: C: 0.03wt%-0.25wt%, Ni: 5.00wt%-6.00wt%, Mo: 4.00wt%-6.00wt%, Cr: 9.00wt%-11.00wt%, Co: 8.00wt%-10.00wt%, and the balance being Fe;

[0023] The volume proportion of the alloy powder is 50%-70%, and the volume proportion of the binder is 30%-50%.

[0024] In some embodiments of the present disclosure, the binder includes, by mass percentage, polyoxymethylene: 60wt%-80wt%, paraffin: 3wt%-8wt%, polyethylene: 3wt%-8wt%, polypropylene: 5wt%-10wt% and the balance stearic acid.

[0025] According to a third aspect of the present disclosure, a method for preparing an alloy steel is provided, the method comprising:

[0026] The alloy powder is mixed with a binder to obtain a composite, wherein the alloy powder comprises: C: 0.03wt%-0.25wt%, Ni: 5.00wt%-6.00wt%, Mo: 4.00wt%-6.00wt%, Cr: 9.00wt%-11.00wt%, Co: 8.00wt%-10.00wt%, and the balance is Fe;

[0027] Under first preset conditions, the composite is kneaded, heated, extruded and crushed to form a feedstock;

[0028] Under the second preset condition, the feed material is injection molded to obtain a green body;

[0029] Under the third preset condition, catalytically debinding the green body to obtain a debinded body;

[0030] Under a fourth preset condition, the debinded blank is subjected to partial pressure sintering to obtain a sintered body;

[0031] Under the fifth preset condition, the sintered body is heat treated to obtain the alloy steel.

[0032] In some embodiments of the present disclosure, the debinded blank is subjected to partial pressure sintering, comprising:

[0033] Placing the debinded blank in a sintering furnace for first sintering, wherein the fourth preset conditions for the first sintering include: a first vacuum degree of 14 KPa-16 KPa, a first heating rate of 3.8°C / min-4.2°C / min, a first sintering temperature of 950°C-1050°C, and a first sintering time of 0.8h-1.2h;

[0034] The debinded blank after the first sintering is subjected to a second sintering, wherein the fourth preset conditions of the second sintering include: a second vacuum degree of 19 KPa-21 KPa, a second heating rate of 2.8° C. / min-3.2° C. / min, a second sintering temperature of 1250° C.-1350° C., and a second sintering time of 1.8 h-2.2 h;

[0035] The debinded blank after the second sintering is subjected to a third sintering, and the fourth preset conditions of the third sintering include: a third vacuum degree of 24KPa-26KPa, a third sintering temperature of 1250°C-1350°C, a third sintering time of 2.8h-3.2h, and cooling with the furnace.

[0036] In some embodiments of the present disclosure, the heat treatment includes solution treatment, cryogenic treatment and aging treatment;

[0037] The fifth preset conditions of the solution treatment include: the solution temperature is 940°C-960°C, the solution time is 1.3h-1.7h, water cooling, and the solution treatment is a secondary solution treatment;

[0038] The fifth preset condition of the cryogenic treatment includes: using liquid nitrogen with a cryogenic temperature of [-200°C, -196°C] for the cryogenic treatment, and the cryogenic time is 0.5h-0.7h;

[0039] The fifth preset conditions of the aging treatment include: an aging temperature of 490° C.-520° C., an aging time of 2.8 h-3.2 h, and furnace cooling.

[0040] In some embodiments of the present disclosure, catalytic degreasing is performed on the green body under the third preset condition, comprising:

[0041] Placing the green body in a degreasing furnace, introducing an inert gas into the degreasing furnace at 110° C.-130° C., wherein the first introduction time of the inert gas is 0.8 h-1.2 h;

[0042] Under the protection of the inert gas, a nitric acid solution is introduced into the degreasing furnace, the flow rate of the nitric acid solution is 2.8 g / min-3.2 g / min, and the second introduction time of the nitric acid solution and the inert gas is 8.8 h-9.2 h;

[0043] After the introduction of the nitric acid solution is stopped, the inert gas is continued to be introduced and the furnace is cooled. The third introduction time of the inert gas is 0.5h-0.7h.

[0044] In some embodiments of the present disclosure, the first preset condition includes: a mixing speed of 110 r / min-130 r / min, a mixing time of 1.4 h-1.6 h, and a mixing temperature of 120° C.-130° C.; and / or,

[0045] The second preset conditions include: injection temperature of 185°C-195°C, injection pressure of 105MPa-115MPa, injection time of 18s-22s, and the temperature of the mold used in the injection molding is 115°C-125°C.

[0046] According to a fourth aspect of the present disclosure, there is provided a rotating shaft, which, in terms of mass percentage of constituent elements, comprises:

[0047] C: 0.03wt%-0.25wt%;

[0048] Ni: 5.00wt%-6.00wt%;

[0049] Mo: 4.00wt%-6.00wt%;

[0050] Cr: 9.00wt%-11.00wt%;

[0051] Co: 8.00wt%-10.00wt%;

[0052] Fe: remainder;

[0053] Among them, the mass percentage ratio X1=(Cr+Mo) / C is 12-566.

[0054] According to a fifth aspect of the present disclosure, an electronic device is provided, comprising a first body, a second body and the rotating shaft provided by the fourth aspect of the present disclosure, wherein the first body and the second body are rotatably connected via the rotating shaft.

[0055] The technical solution provided by the embodiments of the present disclosure may include the following beneficial effects: by improving the composition ratio of the alloy powder for forming the alloy steel, the density of the alloy steel formed by the alloy powder is increased, thereby improving the strength and elongation of the alloy steel. The strength of the alloy steel can exceed 1800MPa and the elongation can exceed 6%, meeting the requirements of high-performance parts.

[0056] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. DETAILED DESCRIPTION

[0058] Metal Injection Molding (MIM) technology is a new powder metallurgy molding technology that introduces modern plastic injection technology into the field of powder metallurgy. MIM technology uses mold injection molding blanks and quickly manufactures high-precision, three-dimensional complex parts through sintering to meet the needs of communication equipment shafts, military equipment parts, high-voltage sensors, etc.

[0059] With the in-depth application of MIM products in various fields, the demand for the strength and toughness of MIM materials continues to increase. At present, the yield strength of low-carbon alloy steels made by MIM technology is mostly around 1500MPa, and the elongation is mostly around 6%. For example, the Chinese invention patent with application number 202010852638.3 discloses an injection molded ultra-high strength steel with a material composition of C <0.1%, Ni 15.5-19.5%, Co 7.0-10.0%, Mo 4.0-6.0%, Ti <1.5%, and the balance is Fe. Although the yield strength can reach 1500MPa, the elongation is only up to 6%, and as the yield strength increases, the elongation decreases. For another example, the Chinese invention patent with application number 202010200648.9 discloses a MIM process for complex corrosion-resistant steel parts. The material composition is C <0.1%, Cr 11.0~15.0%, Ni 10.0~14.0%, Mo 0.5~2.0%, Si <0.5%, Mn <0.5%, Ti 1.0~4.0%, and the remainder is Fe. The elongation of the material after heat treatment is 12~13%, but the yield strength is only 1500MPa. For another example, the Chinese invention patent with application number 201410248360.3 discloses a method for metal powder injection molding high-strength maraging steel, the material composition of which is C≤0.08%, Ni17.0~19.0%, Co8.0~10.0%, Mo 4.5~6.5%, and the balance is Fe and unavoidable impurities. Although the elongation is ≥10%, the strength is still low, and the tensile strength can only reach 1500MPa.

[0060] During the research on the existing MIM low-carbon alloy steel, the inventors found that the MIM low-carbon alloy steel generally has the problem of low grain density, which affects the strength of the low-carbon alloy steel and makes it difficult to meet the requirements of high strength and high toughness at the same time.

[0061] In view of this, the present disclosure provides an alloy powder, which improves the composition ratio of the alloy powder for forming low-carbon high-alloy steel and controls the proportion of carbon elements in the alloy powder within a reasonable range, thereby improving the density of the low-carbon high-alloy steel formed by the alloy powder, thereby improving the strength and elongation of the low-carbon high-alloy steel. The strength of the low-carbon high-alloy steel can exceed 1800MPa and the elongation exceeds 6%, meeting the needs of high-performance parts.

[0062] An exemplary embodiment of the present disclosure provides an alloy powder, which includes, in terms of mass percentage: C: 0.03wt%-0.25wt%; Ni: 5.00wt%-6.00wt%; Mo: 4.00wt%-6.00wt%; Cr: 9.00wt%-11.00wt%; Co: 8.00wt%-10.00wt%; Fe: balance; wherein the mass percentage ratio X1=(Cr+Mo) / C is 12-566.

[0063] It should be noted that each component in the alloy powder is in powder form, that is, the alloy powder includes carbon powder, nickel powder, molybdenum powder, chromium powder, cobalt powder and iron powder, and the total mass percentage of each component is 100%. In the alloy powder, the content of carbon powder is controlled to be less than 0.25wt%, and the total content of alloy elements such as nickel powder, molybdenum powder, chromium powder and cobalt powder is higher than 10wt%, so that the alloy steel formed by the alloy powder is low-carbon high-alloy steel.

[0064] Fe is the main component of alloy steel, and carbon, as one of the important components of alloy steel, can react with elements such as Fe, Cr, and Mo to form metallic compounds, expressed as (Fe, M) 3C, specifically, carbon can react with iron to form cementite. Carbon can also be dissolved in a metal matrix, such as being dissolved in the α-Fe lattice gap and the γ-Fe lattice gap respectively, to affect the properties such as hardness, strength, and toughness of alloy steel. On the one hand, the carbon content in the alloy powder can affect the content of carbides in the alloy steel, and the carbide content in the alloy steel increases, which can improve the strength of the alloy steel. On the other hand, the carbon content in the alloy powder can have a significant impact on the sintering process in the subsequent preparation of the alloy steel process, and when the carbon content increases, the liquid phase generated in the sintering process increases in number, which can promote the sintering densification, and improve the density of the alloy steel finally formed, to achieve the improvement of the strength of the alloy steel. On the other hand, in the alloy powder, at a temperature below 912°C, alloy elements such as C, Ni, Mo, Cr, and Co can be dissolved in the interstitial solid solution of the α-Fe lattice, and the interstitial solid solution formed is called ferrite; at a temperature between 912°C and 1394°C, the interstitial solid solution formed by each alloy element dissolving in the interstitial solid solution of the γ-Fe lattice is called austenite; increasing the carbon content is beneficial to the cooling of the alloy steel during the production process of the alloy steel, so that more carbon atoms in the austenite do not have time to diffuse out of the unit cell, so that more carbon atoms stay in the unit cell, so as to increase the number of martensite formed, which is a supersaturated solid solution of carbon in α-Fe. Since the carbon content in this embodiment is controlled between 0.03wt% and 0.25wt%, the martensite formed is basically in the shape of lath martensite, which has high strength and hardness, and has strong toughness, so that the low-carbon high-alloy steel formed by the alloy powder has good hardness, strength and toughness. In some examples, the mass percentage of carbon powder in the alloy powder is 0.05wt%-0.25wt%. In some examples, the mass percentage of carbon powder in the alloy powder is 0.1wt%-0.25wt%. In some examples, the mass percentage of carbon powder in the alloy powder is 0.15wt%-0.25wt%.

[0065] Cr can increase the hardenability of alloy steel and has a secondary hardening effect, so that the alloy steel has good comprehensive mechanical properties after quenching and tempering, and can improve the hardness and wear resistance of alloy steel without causing the alloy steel to become brittle. In addition, Cr can form alloy cementite (Fe, Cr) 3C with carbon and iron, and Cr can also form alloy carbide Cr7C3 with carbon. Cr7C3 has high stability and is difficult to dissolve in austenite. The carbide in the precipitation state can improve the hardness, strength and toughness of the alloy steel. This embodiment controls the mass percentage of Cr in the alloy powder between 9.00wt%-11.00wt% so that the alloy steel has good wear resistance, and the content of carbides can be adjusted so that the alloy steel has good hardness, strength and toughness. In some examples, the mass percentage of Cr in the alloy powder is 9.50wt%-10.50wt%.

[0066] Mo can increase the hardenability of alloy steel, improve the tempering resistance and tempering stability of alloy steel, and enable alloy steel to be tempered at a higher temperature, thereby more effectively eliminating or reducing the residual stress in the material and improving plasticity. In addition, Mo can form a special carbide MoC with carbon, which has very high stability and hardness, is difficult to dissolve in austenite, and plays a precipitation strengthening role. The precipitated MoC can significantly improve the hardness, strength and toughness of the alloy steel. This embodiment controls the mass percentage of Mo in the alloy powder to be between 4.00wt%-6.00wt% to stabilize the hardenability and strength of the alloy steel. In some examples, the mass percentage of Mo in the alloy powder is 4.50wt%-5.50wt%.

[0067] By reasonably controlling the mass percentage ratio X1=(Cr+Mo) / C between 12-566, the content of alloy carbides Cr7C3 and special carbides MoC in the alloy steel that are difficult to dissolve in austenite can be controlled, so that the precipitated carbides in the alloy steel can significantly improve the hardness, strength and toughness of the alloy steel. In some examples, the mass percentage ratio X1=(Cr+Mo) / C is controlled between 56-320.

[0068] The mechanical mixture of ferrite and cementite is pearlite. Ni can strengthen the ferrite in the alloy steel and refine the pearlite. With the increase of nickel content, the tensile strength of the alloy steel can be improved, and the yield strength can be significantly improved. While improving the strength of the alloy steel, the damage to the toughness, plasticity and other process performance of the alloy steel is less than that of other alloying elements. In addition, nickel can form a continuous solid solution with iron. This embodiment controls the mass percentage of Ni in the alloy powder to be between 5.00wt%-6.00wt% to ensure that the alloy steel has good strength, plasticity and toughness. In some examples, the mass percentage of Ni in the alloy powder is 5.20wt%-5.80wt%.

[0069] Co can coordinate with Mo to make the alloy steel have ultra-high hardness and good comprehensive mechanical properties. Co can also form a continuous solid solution with iron, and Co can strengthen ferrite, and can improve the hardness, yield point and tensile strength of the alloy steel under annealing or normalizing conditions. Since too much Co in the alloy powder can significantly reduce the hardenability of the alloy steel, and at the same time reduce the elongation and impact toughness of the alloy steel, this embodiment reasonably controls the mass percentage of Co in the alloy powder between 8.00wt%-10.00wt% to balance the strength and toughness of the alloy steel. In some examples, the mass percentage of Co in the alloy powder is 8.50wt%-9.50wt%.

[0070] In the technical solution provided in this embodiment, alloy elements such as C, Ni, Mo, Cr, and Co cooperate with each other, Co and Ni significantly improve the strength of alloy steel, and Mo and Cr ensure the hardenability of alloy steel, so that when the alloy steel is cooled during the production process of alloy steel, the speed of precipitation of each alloy atom dissolved in austenite from the unit cell is increased, and an extremely fine second phase is uniformly dispersed and distributed between martensite, resulting in second phase strengthening. In addition, Mo and Cr can also form carbides with C, and carbides can significantly improve the hardness, strength and toughness of alloy steel. C can also be dissolved in the unit cell of iron to form lath martensite with higher strength and toughness. Alloy elements such as C, Ni, Mo, Cr, and Co cooperate with each other, so that the strengthening effect on the material is sufficient to make the yield strength of the alloy steel ≥1700MPa, the ultimate tensile strength ≥1800MPa, and the elongation ≥6%, thereby greatly improving the comprehensive mechanical properties of the material. If the content of Cr, Ni, Mo and Co is lower than the given minimum value, the strengthening effect on the material may be insufficient, while if it is higher than the given maximum value, it will have an adverse effect on the toughness of the material.

[0071] Exemplarily, the average particle size of the alloy powder is controlled to be between 4 μm and 20 μm, so that the powders of each component in the alloy powder can be mixed more evenly, so that the properties of the formed alloy steel have good uniformity. In some examples, the average particle size of the alloy powder is between 4 μm and 10 μm.

[0072] An exemplary embodiment of the present disclosure provides a composite, which consists of an alloy powder and a binder, wherein the alloy powder includes, by mass percentage: C: 0.03wt%-0.25wt%, Ni: 5.00wt%-6.00wt%, Mo: 4.00wt%-6.00wt%, Cr: 9.00wt%-11.00wt%, Co: 8.00wt%-10.00wt%, and the balance is Fe; and in the alloy powder, the mass percentage ratio X1=(Cr+Mo) / C can be between 56-320.

[0073] The binder can impart its viscous flow characteristics to the alloy powder, so that the composite composed of the alloy powder and the binder has good uniformity and fluidity to adapt to the injection molding technology and maintain the shape of the blank obtained by injection molding. For example, the binder can be a binder system commonly used in the MIM process, such as a system based on polyoxymethylene, or a system based on paraffin. In the composite, the volume proportion of the binder can be 50%-70%, and the volume proportion of the binder can be 30%-50%. In some examples, the alloy powder and the binder can be mixed in a volume ratio of 50%:50% to obtain a composite. In other examples, the alloy powder and the binder can be mixed in a volume ratio of 60%:40% to obtain a composite. In other examples, the alloy powder and the binder can be mixed in a volume ratio of 70%:30% to obtain a composite.

[0074] In one example, the binder includes, by mass percentage: polyoxymethylene: 60wt%-80wt%, paraffin: 3wt%-8wt%, polyethylene: 3wt%-8wt%, polypropylene: 5wt%-10wt% and the balance of stearic acid. Polyoxymethylene, polyethylene and polypropylene can grasp the alloy powder particles and play a bonding role between the alloy powder particles. Paraffin acts as a lubricant to reduce the viscosity of the composite. Stearic acid acts as a coupling agent. The functional groups in the coupling agent play a bridging role between the alloy powder particles and polyoxymethylene, polyethylene and polypropylene to enhance the grasping force of these three components on the alloy powder particles. Among them, the cracking temperature and volatilization temperature of polyoxymethylene, polyethylene and polypropylene are not the same, so that in the subsequent removal of the binder, for example, after the polyoxymethylene is cracked, the remaining polyethylene and polypropylene can also play a skeleton support role to ensure that the product still has a certain shape and strength.

[0075] An exemplary embodiment of the present disclosure further provides a method for preparing alloy steel, wherein the method for preparing alloy steel is specifically prepared by MIM technology. Specifically, the method for preparing alloy steel comprises the following steps:

[0076] Step S100, mixing alloy powder with a binder to obtain a composite, wherein the alloy powder includes: C: 0.03wt%-0.25wt%, Ni: 5.00wt%-6.00wt%, Mo: 4.00wt%-6.00wt%, Cr: 9.00wt%-11.00wt%, Co: 8.00wt%-10.00wt%, and the balance is Fe;

[0077] Step S200, under a first preset condition, kneading the composite material, extruding it through heating and crushing it to form a feed material;

[0078] Step S300, injection molding the feed material under the second preset condition to obtain a green body;

[0079] Step S400, under the third preset condition, catalytically debinding the green body to obtain a debinded body;

[0080] Step S500, under the fourth preset condition, performing partial pressure sintering on the degreased blank to obtain a sintered body;

[0081] Step S600: Under the fifth preset condition, heat-treat the sintered body to obtain alloy steel.

[0082] In step S100, the composite obtained by mixing the alloy powder and the binder may be the composite provided by the above embodiment of the present disclosure, and the volume ratio of the alloy powder to the binder may be 50-70%:30%-50%. The alloy powder may be the alloy powder provided by the above embodiment of the present disclosure, including: C: 0.03wt%-0.25wt%, Ni: 5.00wt%-6.00wt%, Mo: 4.00wt%-6.00wt%, Cr: 9.00wt%-11.00wt%, Co: 8.00wt%-10.00wt%, and the balance is Fe, which is not described in detail here.

[0083] In step S200, this step includes mixing and crushing. During mixing, the alloy powder and the binder are mixed to obtain a uniform feed process, and the shape of the feed can determine the performance of the product. The first preset condition can be a condition for the composite to be well mixed, which is preset by the technician, for example, it can include conditions such as mixing temperature and mixing time. Exemplarily, the first preset condition can include a mixing speed of 110r / min-130r / min, a mixing time of 1.4h-1.6h, and a mixing temperature of 120℃-130℃. When the composite is heated and mixed, the binder is heated and in a molten state to uniformly coat the surface of the alloy powder particles to play a bonding role. By controlling the mixing temperature in the first preset condition, the binder is in a molten state, that is, it will not decompose, and the viscosity will not be too low due to partial melting, resulting in the phenomenon of separation of the alloy powder and the binder. By controlling the mixing time and the speed of the mixer in the first preset condition, the composite is subjected to shear force, so that the alloy powder can be mixed evenly. The compound after mixing is extruded from the mixer, and the outlet temperature during extrusion is controlled between 120°C and 130°C so that the compound still has good fluidity. The extruded compound is crushed after air cooling, for example, by a jaw crusher, to obtain a granular feed. Exemplarily, the first preset condition may include a mixing speed of 120r / min, a mixing time of 1.5h, and a mixing temperature of 120°C.

[0084] In step S300, the purpose of injection molding is to obtain a MIM molded green body with a desired shape, no defects, and uniformly arranged particles. First, the granular feed is heated to a certain temperature to make it fluid, then injected into the mold and cooled to obtain a green body with a certain rigidity of the desired shape, and then taken out of the mold to obtain a MIM molded green body. The process of feed injection molding is similar to that of traditional plastic injection molding, but because the feed has a high content of alloy powder, the process parameters of injection molding need to be strictly controlled, and improper control will easily cause various defects.

[0085] The second preset condition may be a condition preset by a technician for feeding to be well injected, for example, it may include conditions such as injection temperature and injection pressure. Exemplarily, the second preset condition may include: injection temperature of 185℃-195℃, injection pressure of 105MPa-115MPa, injection time of 18s-22s, and the temperature of the mold used in injection molding of 115℃-125℃. If the injection temperature is too low, it is easy to be difficult to inject due to insufficient plasticization of the feeding. If the injection temperature is too high, it will cause the polyoxymethylene in the feeding to decompose violently; if the injection pressure is too low, the cavity filling may be insufficient, and if the injection pressure is too high, flash may occur; if the mold temperature is too low, the surface of the green body is prone to weld marks and black lines, and if the mold temperature is too high, the surface of the green body is prone to silver lines. In some examples, the second preset condition may include: injection temperature of 190℃, injection pressure of 110MPa, injection time of 20s, and the temperature of the mold used in injection molding is 120℃.

[0086] In step S400, catalytic degreasing can remove most of the binder in the green body, preventing the green body from cracking, bulging, deformation or collapse during the subsequent sintering process. It should be noted that when the green body is catalytically degreased, an inert gas can be used as a protective atmosphere to avoid oxidation of the alloy powder by reacting with oxygen in the air. At the same time, the degreasing operation can also be adjusted based on the composition of the binder in the green body. For example, for a binder based on polyformaldehyde, nitric acid or oxalic acid can be used as a catalyst for degreasing, and for a binder based on paraffin, solvent degreasing or thermal degreasing can be used. The third preset condition can be a condition pre-set by a technician that is conducive to catalytic degreasing of the green body.

[0087] In some possible implementations, in step S400, catalytic degreasing is performed on the green body under the third preset condition, specifically including:

[0088] Step S410, placing the green body in a degreasing furnace, introducing inert gas into the degreasing furnace at 110° C.-130° C., and the first introduction time of the inert gas is 0.8 h-1.2 h;

[0089] Step S420, under the protection of inert gas, introducing nitric acid solution into the degreasing furnace, the flow rate of the nitric acid solution is 2.8g / min-3.2g / min, and the second introduction time of the nitric acid solution and the inert gas is 8.8h-9.2h;

[0090] Step S430, after stopping the introduction of nitric acid solution, continue to introduce inert gas and cool down the furnace, the third introduction time of inert gas is 0.5h-0.7h.

[0091] In this embodiment, after placing the green body in the degreasing furnace, before introducing the catalyst, the degreasing furnace is heated to between 110°C and 130°C, and an inert gas is introduced into the degreasing furnace for a duration of 0.8h-1.2h to remove the impurities in the degreasing furnace and prevent the alloy powder in the green body from reacting with oxygen in the air and being oxidized during the degreasing process. The inert gas may include one of nitrogen or argon. In some examples, the temperature in the degreasing furnace can be controlled at about 120°C, and the first introduction time of the inert gas can be 1h.

[0092] Furthermore, while the nitric acid solution is introduced into the degreasing furnace, an inert gas is continuously introduced to protect the degreasing process. When the temperature in the degreasing furnace is between 110°C and 130°C, the nitric acid solution can react with polyoxymethylene to decompose it into formaldehyde gas, and the formaldehyde gas forms uniformly distributed flow pores inside the green body to serve as a discharge channel for the subsequent decomposition and volatilization of the remaining binder components. At the same time, after the decomposition of polyoxymethylene, the remaining polyethylene and polypropylene can play a role in skeleton support. The flow rate of the nitric acid solution is controlled between 2.8g / min-3.2g / min, and the second introduction time of the nitric acid solution and the inert gas is between 8.8h-9.2h, that is, the duration of the catalytic reaction is between 8.8h-9.2h, so as to control the decomposition rate of polyoxymethylene within a suitable range, and avoid the violent decomposition of polyoxymethylene, resulting in cracks or bulging defects such as degreasing blanks. In some examples, the flow rate of the nitric acid solution can be controlled at about 3.0g / min, and the duration of the catalytic reaction can be controlled at about 9.0h. It is understandable that the formaldehyde gas after the decomposition of polyoxymethylene can be transmitted to the exhaust gas treatment device for harmless treatment before being discharged.

[0093] After the nitric acid solution is stopped, that is, after the polyoxymethylene catalytic reaction is completed, since the temperature in the degreasing furnace is still between 110°C and 130°C, in order to prevent the alloy powder in the degreasing blank from reacting with oxygen in the air and being oxidized, the inert gas is continued to be introduced into the degreasing furnace, and the degreasing furnace is controlled to stop heating, so that the temperature of the degreasing blank and the degreasing furnace is naturally cooled under the protection of the inert gas. Exemplarily, after the nitric acid solution is stopped, the inert gas is continuously introduced for 0.5h-0.7h, so that the degreasing blank can be fully cooled naturally.

[0094] In step S500, the sintering process can remove part of the remaining binder in the degreased blank, and at the same time, it can eliminate the pores between the alloy powders, and promote the growth of metal grains under high temperature and pressure, so that the sintered body obtained by sintering reaches or approaches full densification, and improves the strength of the obtained alloy steel. In this step, the degreased blank is subjected to partial pressure sintering. Partial pressure sintering refers to adjusting the gas pressure or vacuum pressure in the sintering furnace at different stages of sintering, and the pressure of the sintering fixture can also be adjusted so that the degreased blank can be sintered based on different pressures. Partial pressure sintering can make the alloy powder more closely combined, improve the density of the obtained sintered body, and improve the mechanical properties of the sintered body such as strength and hardness, and can also reduce the porosity of the sintered body, and improve the corrosion resistance and wear resistance of the sintered body. The fourth preset condition may include the distinguishing time of different sintering stages, the pressure and temperature of each sintering stage, and so on.

[0095] In some possible implementations, in step S500, the debinded blank is subjected to partial pressure sintering, specifically comprising:

[0096] Step S510, placing the debinded blank in a sintering furnace for first sintering, the fourth preset conditions for the first sintering include: a first vacuum degree of 14 KPa-16 KPa, a first heating rate of 3.8°C / min-4.2°C / min, a first sintering temperature of 950°C-1050°C, and a first sintering time of 0.8h-1.2h;

[0097] Step S520, performing a second sintering on the debinded blank after the first sintering, the fourth preset conditions of the second sintering include: a second vacuum degree of 19KPa-21KPa, a second heating rate of 2.8°C / min-3.2°C / min, a second sintering temperature of 1250°C-1350°C, and a second sintering time of 1.8h-2.2h;

[0098] Step S530, performing a third sintering on the degreased blank after the second sintering, the fourth preset conditions of the third sintering include: a third vacuum degree of 24KPa-26KPa, a third sintering temperature of 1250°C-1350°C, a third sintering time of 2.8h-3.2h, and cooling with the furnace.

[0099] In step S510, the degreased blank is placed in a sintering jig. The sintering jig can be a jig that is resistant to high temperatures and does not react with metals at high temperatures, such as a 99 porcelain sintering jig. The sintering jig containing the degreased blank is placed in a sintering furnace for the first sintering. The first sintering stage is mainly used to remove residual binders such as paraffin, polypropylene, polyethylene, etc. in the degreased blank. When performing the first sintering, the corresponding fourth preset conditions include a first vacuum degree of 14KPa-16KPa, a first heating rate of 3.8℃ / min-4.2℃ / min, a first sintering temperature of 950℃-1050℃, and a first sintering time of 0.8h-1.2h.

[0100] The first vacuum degree can be, for example, about 15KPa. Controlling the vacuum degree in the sintering furnace can prevent the debinding blank from reacting with oxygen in the air and being oxidized during the sintering process. Since there are evenly distributed flow pores formed when formaldehyde gas volatilizes inside the debinding blank, the heating rate during the first sintering is controlled between 3.8℃ / min-4.2℃ / min, for example, 4.0℃ / min, which can prevent the sintered body from producing defects such as cracks or bulges while increasing the volatilization rate of low molecular weight components such as polyethylene and polypropylene. With the first heating rate, the temperature in the sintering furnace is raised to the first sintering temperature between 950℃-1050℃. The first sintering temperature can be controlled at 1000℃, and the first sintering time is kept between 0.8h-1.2h, for example, about 1h, so as to remove the residual binder in the debinding blank as much as possible.

[0101] In step S520, after the debinding blank is kept at the first sintering temperature for the first sintering time, that is, after the first sintering, the vacuum degree, sintering temperature and heating rate in the sintering furnace are adjusted to perform the second sintering. The fourth preset conditions for the second sintering include: the second vacuum degree is 19KPa-21KPa, the second heating rate is 2.8℃ / min-3.2℃ / min, the second sintering temperature is 1250℃-1350℃, and the second sintering time is 1.8h-2.2h.

[0102] Since the binder in the debinded blank after the first sintering is removed, the vacuum degree in the sintering furnace is increased to between 19KPa-21KPa, for example, about 20KPa, so that the density and mechanical properties of the debinded blank after the second sintering are improved. During the second sintering, the sintering temperature is increased from about 1000℃ to a second sintering temperature between 1250℃-1350℃ at a second heating rate between 2.8℃ / min-3.2℃ / min. The second heating rate can be controlled at about 3.0℃ / min, for example, and the second sintering temperature can be controlled at about 1300℃. The second heating rate is less than the first heating rate to avoid excessively fast grain growth rate, resulting in a large grain diameter, which has an adverse effect on the strength and elongation of the product. At the same time, the second sintering temperature is controlled between 1250℃-1350℃ to avoid the material failing to densify due to too low a temperature, or overburning or melting due to too high a temperature. The second sintering temperature is maintained for a period of 1.8 hours to 2.2 hours, such as about 2 hours, to complete the second sintering.

[0103] In step S530, after the debinded blank is kept at the second sintering temperature for the second sintering time, that is, after the second sintering, the vacuum degree, sintering temperature and heating rate in the sintering furnace are adjusted to perform the third sintering. The fourth preset conditions of the third sintering include: the third vacuum degree is 24KPa-26KPa, the third sintering temperature is 1250℃-1350℃, and the third sintering time is 2.8h-3.2h.

[0104] The third sintering temperature during the third sintering can be the same as the second sintering temperature, but the vacuum degree in the sintering furnace is increased from 19KPa-21KPa to 24KPa-26KPa, for example, adjusted to about 25KPa, to further improve the density and mechanical properties of the sintered body obtained after the third sintering. The third sintering temperature is kept at a temperature of 2.8h-3.2h, for example, about 3h, to complete the third sintering. After the third sintering is completed, it is naturally cooled with the furnace to obtain a densified sintered body.

[0105] In step S600, in order to improve the strength and toughness of the sintered body, the sintered body is heat treated under the fifth preset condition to obtain an alloy steel with good strength and elongation. The heat treatment may include, for example, oil quenching and tempering treatment, solution treatment, failure treatment, cryogenic treatment and other heat treatment processes to increase strength. Based on different treatment processes, the corresponding fifth preset conditions are different.

[0106] In some possible embodiments, the heat treatment includes solution treatment, cryogenic treatment and aging treatment. The fifth preset condition for controlling the solution treatment is that the solution temperature can be between 940°C and 960°C, and the solution time can be between 1.3h and 1.7h. In some examples, the solution temperature can be 950°C, and the holding time of the solution treatment can be 1.5h. The solution treatment can make the components in the sintered body dissolve evenly into the matrix to form a uniform austenite structure solid solution, thereby improving the elongation of the formed alloy steel. In conjunction with the water cooling operation, the alloy steel is cooled rapidly so that the austenite is quickly converted into martensite so that the alloy steel has good hardness, strength and toughness. When performing the solution treatment, two repeated solutions are performed, that is, the sintered body is in a heat treatment furnace, and after being kept at 940°C-960°C for 1.3h-1.7h, it is water-cooled, and then the water-cooled sintered body is repeatedly dissolved and water-cooled once to improve the uniformity of the solid solution.

[0107] Cryogenic treatment can completely transform martensite, inhibit martensite from reversing to austenite, precipitate ultrafine carbides on the martensite matrix, improve the uniformity of the structure, and ensure that the alloy steel obtains a fully martensitic structure after cryogenic treatment. The fifth preset condition for cryogenic treatment includes: cryogenic treatment using liquid nitrogen at a cryogenic temperature of [-200°C, -196°C], and the cryogenic time is 0.5h-0.7h. In some examples, the liquid nitrogen temperature is -196°C, the cryogenic time is 0.5h, and then the cryogenically treated sintered body is placed in the air to warm up to room temperature.

[0108] The sintered body after deep cryogenic treatment is placed in an aging furnace, the aging furnace is controlled to be a vacuum environment, and the temperature of the aging furnace is controlled to be between 490°C and 520°C, for example, 500°C, and the sintered body with a full martensite structure is heated to an intermediate temperature lower than its transformation temperature to austenite, so that carbides are further precipitated, so as to further improve the hardness, strength and elongation of the obtained alloy steel.

[0109] In order to more clearly explain the technical solution of the present disclosure, the test performance of the alloy steel made from the alloy powder provided by the present disclosure is described in detail below in combination with specific embodiments, wherein the samples for performance testing in each embodiment are alloy rods made from the alloy powder by MIM process.

[0110] Table 1 Formula and properties of alloy steels of Examples 1 to 7

[0111] Example Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 C (wt%) 0.175 0.175 0.175 0.175 0.175 0.03 0.05 Ni(wt%) 5.56 5.56 5.56 5.56 5.56 5.94 5.46 Mo (wt%) 4.8 4.8 4.8 4.8 4.8 4.09 5.37 Cr(wt%) 9.8 9.8 9.8 9.8 9.8 9.17 10.94 Co(wt%) 8.67 8.67 8.67 8.67 8.67 8.24 9.21 Fe(wt%) 70.995 70.995 70.995 70.995 70.995 72.53 68.97 Tensile strength(MPa) 1898.5 1892.4 1915.4 1918 1901.9 1876.1 1881.7 Yield strength(MPa) 1736.1 1703.8 1769.9 1766.4 1756.94 1714.2 1721.6 Tensile modulus(GPa) 203.04 182.07 193.12 193.28 190.4 185.53 191.31 Elongation(%) 6.04 6.36 6.56 6.52 6.44 6.29 6.09

[0112] Table 2 Formulation and properties of alloy steels of Examples 8 to 14

[0113]

[0114]

[0115] Among them, tensile strength, yield strength, tensile modulus and elongation are all carried out in accordance with the reference standard GB / T 228.1-2010. The size specifications of the alloy steel formed in each embodiment are the same, and the sources of the raw material powders in the alloy powder are also the same. It should be noted that Examples 1-5 are alloy rods of the same batch formed by the same formula and the same process. Due to the differences in the positions placed in the processing equipment during catalytic degreasing, sintering and heat treatment, there are slight differences in their performance. The alloy steel made from the alloy powder provided in the present disclosure has high tensile strength, yield strength and elongation, tensile strength ≥1800MPa, yield strength ≥1700MPa, elongation ≥5%, and tensile modulus ≥180GPa, which meets the requirements of high strength and high toughness of MIM materials.

[0116] An exemplary embodiment of the present disclosure also provides a structural part, which is made of the alloy powder provided in the above embodiment of the present disclosure through the MIM process. Exemplarily, in terms of the mass percentage of the constituent elements, the structural part includes: C: 0.03wt%-0.25wt%; Ni: 5.00wt%-6.00wt%; Mo: 4.00wt%-6.00wt%; Cr: 9.00wt%-11.00wt%; Co: 8.00wt%-10.00wt%; Fe: balance; wherein the mass percentage ratio X1=(Cr+Mo) / C is 12-566. The structural part can be a structural part in an electronic device, such as a foldable electronic device hinge, a hinge, a camera bracket, a USB port, a lifting camera base, and a transmission part.

[0117] In some embodiments, the structural member is a rotating shaft. Specifically, part of the rotating shaft may be made of the alloy powder provided by the present disclosure, or the entire rotating shaft may be made of the alloy powder provided by the present disclosure. The specific structure of the rotating shaft can be set according to actual needs, and the present disclosure does not specifically limit it. The rotating shaft provided by the present disclosure has high tensile strength, yield strength and elongation, which can improve the stability of the foldable electronic device.

[0118] An exemplary embodiment of the present disclosure also provides an electronic device, which may be a foldable mobile phone, a laptop computer, or other device with a rotation connection requirement. The electronic device includes a main body, a second main body, and a rotating shaft provided by the present disclosure, wherein the first main body is connected to one end of the rotating shaft, and the second main body is connected to the other end opposite to the rotating shaft, and the first main body and the second main body can be rotationally connected through the rotating shaft, so that the electronic device can be opened in different ways such as folding and folding. Since the rotating shaft has high tensile strength, yield strength, and elongation, the electronic device has good stability and a long life, which improves the user experience.

[0119] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed in this disclosure. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.

Claims

1. An alloy powder, characterized in that: In terms of mass percentage, the alloy powder comprises: C: 0.03wt%-0.25wt%; Ni: 5.00wt%-6.00wt%; Mo: 4.00wt%-6.00wt%; Cr: 9.00wt%-11.00wt%; Co: 8.00wt%-10.00wt%; Fe: remainder; Among them, the mass percentage ratio X1=(Cr+Mo) / C is 12-566.

2. The alloy powder according to claim 1, characterized in that In terms of mass percentage, the alloy powder comprises: C: 0.05wt%-0.25wt%; Ni: 5.20wt%-5.80wt%; Mo: 4.50wt%-5.50wt%; Cr: 9.50wt%-10.50wt%; Co: 8.50wt%-9.50wt%; Fe: remainder; Among them, the mass percentage ratio X1=(Cr+Mo) / C is 56-320.

3. The alloy powder according to claim 1 or 2, characterized in that: The particle size of the alloy powder is 4-20 μm.

4. A composite, characterized in that The composite comprises alloy powder and a binder, wherein the alloy powder comprises: C: 0.03wt%-0.25wt%, Ni: 5.00wt%-6.00wt%, Mo: 4.00wt%-6.00wt%, Cr: 9.00wt%-11.00wt%, Co: 8.00wt%-10.00wt%, and the balance is Fe; The volume proportion of the alloy powder is 50%-70%, and the volume proportion of the binder is 30%-50%.

5. The composite according to claim 4, characterized in that In terms of mass percentage, the binder includes: polyoxymethylene: 60wt%-80wt%, paraffin: 3wt%-8wt%, polyethylene: 3wt%-8wt%, polypropylene: 5wt%-10wt% and the balance of stearic acid.

6. A method for preparing alloy steel, characterized in that: The preparation method of the alloy steel comprises: The alloy powder is mixed with a binder to obtain a composite, wherein the alloy powder comprises: C: 0.03wt%-0.25wt%, Ni: 5.00wt%-6.00wt%, Mo: 4.00wt%-6.00wt%, Cr: 9.00wt%-11.00wt%, Co: 8.00wt%-10.00wt%, and the balance is Fe; Under first preset conditions, the composite is kneaded, heated, extruded and crushed to form a feedstock; Under the second preset condition, the feed material is injection molded to obtain a green body; Under the third preset condition, catalytically debinding the green body to obtain a debinded body; Under a fourth preset condition, the debinded blank is subjected to partial pressure sintering to obtain a sintered body; Under the fifth preset condition, the sintered body is heat treated to obtain the alloy steel.

7. The method for preparing alloy steel according to claim 6, characterized in that: The debinded blank is subjected to partial pressure sintering, comprising: Placing the debinded blank in a sintering furnace for first sintering, wherein the fourth preset conditions for the first sintering include: a first vacuum degree of 14 KPa-16 KPa, a first heating rate of 3.8°C / min-4.2°C / min, a first sintering temperature of 950°C-1050°C, and a first sintering time of 0.8h-1.2h; The debinded blank after the first sintering is subjected to a second sintering, wherein the fourth preset conditions of the second sintering include: a second vacuum degree of 19 KPa-21 KPa, a second heating rate of 2.8° C. / min-3.2° C. / min, a second sintering temperature of 1250° C.-1350° C., and a second sintering time of 1.8 h-2.2 h; The debinded blank after the second sintering is subjected to a third sintering, and the fourth preset conditions of the third sintering include: a third vacuum degree of 24KPa-26KPa, a third sintering temperature of 1250°C-1350°C, a third sintering time of 2.8h-3.2h, and cooling with the furnace.

8. The method for preparing alloy steel according to claim 6, characterized in that: The heat treatment includes solution treatment, cryogenic treatment and aging treatment; The fifth preset conditions of the solution treatment include: the solution temperature is 940°C-960°C, the solution time is 1.3h-1.7h, water cooling, and the solution treatment is a secondary solution treatment; The fifth preset condition of the cryogenic treatment includes: using liquid nitrogen with a cryogenic temperature of [-200°C, -196°C] for the cryogenic treatment, and the cryogenic time is 0.5h-0.7h; The fifth preset conditions of the aging treatment include: an aging temperature of 490° C.-520° C., an aging time of 2.8 h-3.2 h, and cooling with the furnace.

9. The method for preparing alloy steel according to claim 6, characterized in that: Under the third preset condition, the green body is subjected to catalytic degreasing, comprising: Placing the green body in a degreasing furnace, introducing an inert gas into the degreasing furnace at 110° C.-130° C., wherein the first introduction time of the inert gas is 0.8 h-1.2 h; Under the protection of the inert gas, a nitric acid solution is introduced into the degreasing furnace, the flow rate of the nitric acid solution is 2.8 g / min-3.2 g / min, and the second introduction time of the nitric acid solution and the inert gas is 8.8 h-9.2 h; After the introduction of the nitric acid solution is stopped, the inert gas is continued to be introduced and the furnace is cooled. The third introduction time of the inert gas is 0.5h-0.7h.

10. The method for preparing alloy steel according to claim 6, characterized in that: The first preset conditions include: a mixing speed of 110 r / min-130 r / min, a mixing time of 1.4 h-1.6 h, and a mixing temperature of 120° C.-130° C.; and / or, The second preset conditions include: injection temperature of 185°C-195°C, injection pressure of 105MPa-115MPa, injection time of 18s-22s, and the temperature of the mold used in the injection molding is 115°C-125°C.

11. A rotating shaft, characterized in that: In terms of mass percentage of constituent elements, the rotating shaft comprises: C: 0.03wt%-0.25wt%; Ni: 5.00wt%-6.00wt%; Mo: 4.00wt%-6.00wt%; Cr: 9.00wt%-11.00wt%; Co: 8.00wt%-10.00wt%; Fe: remainder; Among them, the mass percentage ratio X1=(Cr+Mo) / C is 12-566.

12. An electronic device, characterized in that: The electronic device comprises a first body, a second body and the rotating shaft according to claim 11, and the first body and the second body are rotatably connected via the rotating shaft.

Citation Information

Patent Citations

  • Metal powder injection molded high-strength martensite aged steel and preparation method thereof

    CN103981436A

  • Corrosion-resistant steel powder, ultra-high-strength steel feed and preparation process of corrosion-resistant steel complex parts

    CN111304535A

  • Corrosion-resistant steel powder, ultrahigh-strength steel feed and corrosion-resistant steel complex part preparation process

    CN111992704A